Resveratrol protects against renal ischemia/reperfusion injury: A systematic review and meta-analysis of preclinical studies - Li-Hua Wu; Bo Qu; Ling Wu; Yu Liu; Ting Jiang; Ming-Quan Li (Elsevier, 2022)
Renal ischemia/reperfusion (I/R) injury is a major cause of acute kidney injury (AKI). Apart from dialysis, there are currently no satisfactory techniques or medications developed to limit injury or to promote recovery and survival in patients with AKI. Resveratrol (RVT) has been found to have potential benefits in animal models of renal I/R injury. The purpose of this study was to assess the preclinical evidence for RVT therapy in animal models of renal I/R injury, as well as the potential mechanism of action. From conception through April 2021, the MEDLINE (Ovid), Embase, and BIOSIS Previews databases were searched for preclinical studies comparing RVT vs. placebo. A total of seventeen studies involving 255 animals were included in the study. Each study received a score ranging from 4 to 7. Stata/MP 16.0 software was used to perform data analyses. Meta-analysis revealed that RVT treatment reduced serum creatinine levels (p<0.0001), blood urea nitrogen levels (p<0.0001) and renal histology scores when compared to the control (P < 0.0001). Resveratrol's antioxidant, anti-inflammatory, and anti-apoptotic properties were all possible modes of action. The findings suggested that resveratrol may be a promising nephroprotective drug in the treatment of renal I/R injury, thus may contribute to future clinical trials. However, the limitations of this study merit attention: low methodological quality, significant risk of bias, and low evidence quality. Large animal studies or randomized controlled trials will add more evidence and provide a rationale for clinical use.